Comparison of stress distribution on dental implant with different abutment types. (2021) - Jayakumar, N.; Senthilkumar, G.; Vigneshwaran, S.; Ajay Kumar, K.G.
Abstract: Dental implants have a triumph pace of 90–98%, which in clinical terms is essentially high. Implant failure may occur at earlier or later stage. In assessment of the drawn-out accomplishment of a dental implant, the reliability and the stability of the implant–abutment play a vital role. In general, the achievement of the treatment relies upon numerous factors influencing the implant, implant–abutment and abutment–prosthesis interfaces. Early implant failure occurs due to the improper mechanical stability. This study researches the stress distribution in an implant with different implant abutments with different height and angle in different loading criteria. The abutment heights are 5.50 mm, 3.50 mm and 3.60 mm respectively. The loading conditions are applied in vertical and 30˚ angle with the value of 36 N & 100 N. Cobalt chromium alloy is used which has the superior properties like high stiffness, tightly polished, wear resistant and also it is used to avoid crevice corrosion. Computational models of abutment types with different heights were modeled using CAD software and Analyzed with FEA software for finding out the total deformation, Maximum principle stress, and Maximum shear stress. Based on the structure of a dental implant system, it gives significant performance. The minimum and maximum total deformation, Maximum principle stress, and Maximum shear stress were noted in the Type 3 under 36 N vertical condition and Type 1 under 100 N under 30˚ respectively.